Evaluation on Accessibility and Usage of Information and Communication Technology (ICT): Insights from Smallholders in Johor, Malaysia - Yaakub, Nadzifah; Arif Bin Ab Aziz, Amirul; Abdul Fatah, Fazleen (International Journal of Engineering and Technology, 2018)
In todayâ€™s age of modernization, Information and Communication Technology (ICT) has played a very important role in the development of agriculture sector. This technology has brought a significant change in agricultural development where farmers can directly communicate with traders, government, buyers, and producers. However, due to lack of knowledge and information, farmers are not getting the benefits from these technologies. To understand this, a study was conducted to find out the level of accessibility of ICTs among smallholder farmers. To further understand this issue, the study aims to determine the determinants or critical factors that influence the level of ICT accessibility among oil palm smallholders. A random sampling technique was used to select a total of 85 smallholders in the study area while an administered structured interview schedule on the selected respondents were used for data collection. Frequency counts, percentages and a multiple regression analysis were used in the data analysis. Results revealed that majority of the respondents were males (96.5%), a high percentage (71.8%) chose to use personal computer as their ICT tools while 24% used mobile phone to get access or gain more agricultural and inputs information. The paper concluded that network factor and socio-economics such as age and educational level were the most significant factors that influenced the accessibility of ICTs among oil palm smallholders in Johor, West Malaysia.Â Â